2020
DOI: 10.1039/d0gc02293d
|View full text |Cite
|
Sign up to set email alerts
|

A unique pathway to platform chemicals: aldaric acids as stable intermediates for the synthesis of furandicarboxylic acid esters

Abstract: 2,5-Furandicarboxylic acid (FDCA) has received attention as an emerging bio-based building block with many applications, especially in renewable polyesters. The common route to FDCA uses the unstable 5-hydroxymethylfurfural (HMF) as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…The calculated K e at each T is listed in Table 3, and it was found that K e increased with T. The relationship between K e and T agreed well with the Van't Hoff equation, as shown in Eqn (9):…”
Section: Enzymatic Esterification Kineticssupporting
confidence: 67%
See 2 more Smart Citations
“…The calculated K e at each T is listed in Table 3, and it was found that K e increased with T. The relationship between K e and T agreed well with the Van't Hoff equation, as shown in Eqn (9):…”
Section: Enzymatic Esterification Kineticssupporting
confidence: 67%
“…Consequently, lignocellulose is being considered as one of the most promising candidates to replace traditional fossil hydrocarbons as the primary source of stock materials in industry 3–5 . Furfural (FF) is one of the essential platform compounds derived from lignocellulose, and several important commodity chemicals can be prepared through its oxidation, ring‐opening, esterification, hydrogenation, halogenation, and polymerization 6–10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22–24 The third type comprises sugar acids, such as 5-keto- l -galactonic acid and galactaric acid, which can be used to prepare the bio-based platform compounds 5-formyl-2-furancarboxylic acid (FFCA, O/C = 0.67) and 2,5-furandicarboxylic acid (FDCA, O/C = 0.83). 25,26 Further oxidation of FFCA and FDCA is easier due to their natural carboxyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…19 More recently, silica-supported sulfonic acids were also employed for converting Gal into a mixture of 2-furanmonocarboxylates and 2,5-furandicarboxylates. 20 Under the best-found reaction conditions FDCA butyl esters were achieved in a twostep approach (Scheme 2a) encompassing galactaric acid esterification in the presence of butanol (24 h) followed by its cyclisation/aromatization reaction at 220 °C (4 h). FDCA esters were achieved in 80% yield, although this value includes the mono and dibutyl furandicarboxylates.…”
mentioning
confidence: 99%